Within-Population Isotopic Niche Variability in Savanna Mammals: Disparity between Carnivores and Herbivores - Codron, Daryl; Codron, Jacqueline; Sponheimer, Matt; Clauss, Marcus (Frontiers in Ecology and Evolution, 2016)
Large mammal ecosystems have relatively simple food webs, usually comprising three – and sometimes only two – trophic links. Since many syntopic species from the same trophic level therefore share resources, dietary niche partitioning features prominently within these systems. In African and other subtropical savannas, stable carbon isotopes readily distinguish between herbivore species for which foliage and other parts of dicot plants (13C-depleted C3 vegetation) are the primary resource (browsers) and those for which grasses (13C-enriched C4 vegetation) are staples (grazers). Similarly, carbon isotopes distinguish between carnivore diets that may be richer in either browser, grazer, or intermediate-feeding prey. Here, we investigate levels of carbon and nitrogen isotopic niche variation and niche partitioning within populations (or species) of carnivores and herbivores from South African savannas. We emphasize predictable differences in within-population trends across trophic levels: we expect that herbivore populations, which require more foraging effort due to higher intake requirements, are far less likely to display within-population resource partitioning than carnivore populations. Our results reveal generally narrower isotopic niche breadths in herbivore than carnivore populations, but more importantly we find lower levels of isotopic differentiation across individuals within herbivore species. While these results offer some support for our general hypothesis, the current paucity of isotopic data for African carnivores limits our ability to test the complete set of predictions arising from our hypothesis. Nevertheless, given the different ecological and ecophysiological constraints to foraging behaviour within each trophic level, comparisons across carnivores and herbivores, which are possible within such simplified foodwebs, make these systems ideal for developing a process-based understanding of conditions underlying the evolution of intra-specific, individual-level separation of ecological niches.